Selective recovery of uranium from Ca-Mg uranates by chlorination - Pomiro, Federico J.; Gaviría, Juan Pablo; Quinteros, Raúl D.; Bohe, Ana Ester (Elsevier Science, 2017)
Fil: Pomiro, Federico J.. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina